Peningkatan Bidang Pendidikan di kalangan Masyarakat Desa Batu Rata - Nindya Mirandani Pratiwi; Astri Angraeni; Niki Selvia; Zulfan Baihaqi; Siti Maysarah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This Regular Real Work Lecture (KKN) is an activity based on community empowerment and the real form of students in implementing the Tri Dharma of Higher Education, namely in the aspect of community service. With this Regular Real Work Lecture (KKN) as a form of our service in Batu Rata Village, Bangun Purba District, Deli Serdang Regency. This research was conducted in Hamlet 03 Batu Rata village. This method uses a qualitative method in which we conduct observations, interviews and documentation. This study aims to determine the role of Regular Real Work Lectures (KKN) in various fields including the field of Education which we carry out in Batu Rata Village. We see very serious problems in the field of education, including in terms of reading there are still some children who are illiterate, cannot write and count, this is due to the lack of teaching staff and the lack of parental care for their children who are illiterate and numbers. This service is carried out face-to-face with the child. The results of this study indicate that the Regular Community Service Program is a form of our service to the community in order to continue to increase the enthusiasm for learning and help children understand the lessons that have been given. Keywords: Children, KKN, Education.